Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae) - Hardy, Martin (Zootaxa, 2017)
A new species of Bothynus Hope, 1837 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) is described from the eastern Andes in South America. The new species is unique in the genus for having the elytra and part of the pronotum covered with small setae.